1981
DOI: 10.1136/oem.38.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive magnetopneumographic determination of lung dust loads in steel arc welders.

Abstract: Magnetopneumography was used to measure non-invasively the concentration of the ferrimagnetic fraction of retained welding fume in the thoraces of steel arc welders. This was done by measuring the remanent magnetic fields due to ferrimagnetic particles. The 11 welders studied had concentrations of thoracic ferrimagnetic mineral several orders of magnitude greater than three machinists, 16 former asbestos insulators, and 24 control subjects. These concentrations correlated well with total years welding (p < 0-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…Artefacts associated with respiration are commonly observed in biomagnetic recordings and have been attributed to motion associated with magnetic contaminants in the lungs. [54][55][56] In our study, respiration, which occurs at a frequency much higher than the normal gastric frequency, did not affect the signal substantially. Thus, we believe that the primary benefit of suspension of respiration as we required of the subjects in this study is the concomitant reduction in subject motion that leads to a higher fidelity magnetic signal.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Artefacts associated with respiration are commonly observed in biomagnetic recordings and have been attributed to motion associated with magnetic contaminants in the lungs. [54][55][56] In our study, respiration, which occurs at a frequency much higher than the normal gastric frequency, did not affect the signal substantially. Thus, we believe that the primary benefit of suspension of respiration as we required of the subjects in this study is the concomitant reduction in subject motion that leads to a higher fidelity magnetic signal.…”
Section: Discussioncontrasting
confidence: 46%
“…Artefacts associated with respiration are commonly observed in biomagnetic recordings and have been attributed to motion associated with magnetic contaminants in the lungs 54–56 . In our study, respiration, which occurs at a frequency much higher than the normal gastric frequency, did not affect the signal substantially.…”
Section: Discussionmentioning
confidence: 40%
“…21-23 Among them, welders have shown the highest level of lung magnetisability. 21 Subjects without occupational exposure to dust showed negligible or low activities of lung magnetisability compared with welders. 21 22 No lifestyle factors are known to result in measurable magnetisability, although smoking can delay the lung clearance of magnetisable dust in occupationally exposed workers.…”
Section: Discussionmentioning
confidence: 95%
“…Cohen et al [13] observed a significant relation between asbestos retention in the lungs and the exposure index in asbestos miners and combustion workers. The compensated ex-miners were found to present with more intensive RMF than were miners and healthy nonexposed persons [14].…”
Section: Lung Magnetometry In Humansmentioning
confidence: 99%